Türkiye’de sağlık hizmetleri ve sağlık harcamaları - Karagöz, Sevda (My University, 2015)
Dünyadaki bütün ülkeler, sağlıklı birey ve sağlıklı bireylerden oluşan bir toplum gerçekleştirmeyi hedef alır. Bir ülkenin ekonomisinin güçlü olması, ekonomik büyümenin sağlanıp sürdürülebilir kılınması için sağlıklı bir topluma sahip olunması gerekir. Sağlık ekonomisinin bugünkü gelişimi son yirmi yıla dayandırılabilir. Dünyada sağlık ekonomisinin gelişiminin ilk basamağı İkinci Dünya Savaşı’ndan sonra 1950’lerden sonra ABD’de tıp fakültelerinde bağımsız bir ders olarak okutulmaya başlanması kabul edilmektedir. Türkiye’de ise sağlık sektörü dünyadaki gelişmelere paralel olarak gelişememiş ve yaklaşık 40 yıllık bir gecikme ile Türkiye’nin gündemine girebilmiştir. OECD ile karşılaştırılabilir çalışmalar ise 2000’li yıllarda olmuştur. En kapsamlı ilk sağlık politikası çalışması ise 1993 yılında yapılmıştır. Türkiye’de sağlık hizmetleri, 1982 Anayasası’nın 56. Maddesi ile devletin sunmakla yükümlü olduğu bir hizmet olmaktan çıkarılmış ve devlet ‘ herkesin hayatını, beden ve ruh sağlığı içinde sürdürmesini sağlamak; insan ve madde gücünde tasarruf ve verimi arttırarak, işbirliğini gerçekleştirmek amacıyla sağlık kuruluşlarını tek elden planlayıp hizmet vermesini’ düzenlemekle görevlendirilmiştir. Türkiye sağlık konusunda güçlü yönlere ve fırsatlara sahipken; aynı zamanda zayıf yönlere ve tehditlere de sahiptir. Uyguladığı sağlık politikalarıyla bu zayıf yönleri güçlü yönlere ve tehditleri fırsatlara çevirmelidir. Çünkü sağlıklı toplum; nitelikli insan kaynağı ve dolayısıyla kalkınma için çok büyük öneme sahiptir.

All the countries in the world aim to have a society that would consist of healthy individuals. A country need to have a healthy society for a strong economy and a sustainable economic growth for their citizens. The recent progress in the development of medical economy has been formed fort he last two dacedes. The first step of this development of the medical economy was gained acceptance after the World War Two. And after 1950’s when it was taught as an independent lesson in the univercities of ABD. And in Turkey, these progresses as the developments in the medical sector were not developed in paralel with the development in the world, and also , it was entered into Turkey’s agenda with 40 years delay. The works which were comparable with the OECD, were occured in 2000. The very first and the most extensive work on the medical policy , was done in 1993. The medical service, in Turkey were abragated by the low with the 56.theme of the 1982’s constitution. For the reason that it was no more an abligation which goverment has to provide for a a service. And instead of that, the goverment planned and assigned all the medicall institution to become under a one administration to provide a life that all people would have a healthy body and soul, and improve the efficiency and savings in the meterial force and people and lastly perform a good collaboration. Turkey has a strong sides and oppırtunities about medical ıssues. On the other hand, it also has weak sides and treats. There fore, Turkey should turn these weak sides in to strong sides and also turn thede treats into oppırtunities by the medical policies which ara being used in Turkey. Thus, A heathy society has a very important role for the ecomomy and also for the well-qualified people as a source.
Keywords: Ekonomi; İktisat; Sağlık; Türkiye